Kritik Arus Bawah: Studi Wisata Festival di Perbatasan Sota, Merauke - Machya Astuti Dewi; Iva Rachmawati; Sri Issundari; Meilan Sugiarto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat UPN Veteran Yogyakarta, 2020)
Many people believe that organizing festivals in the border area will increase the popularity of the border area and improve the socio-economic conditions of the border communities. But in the case of Sota border area, it is debatable. This paper aims to analyze the views of the community and local government about the border festival which was held by the central government in Sota, Merauke, Papua in 2016 and subsequently explored their views on what border festival should be like. To answer the question, a Focus Group Discussion was conducted with community leaders in Sota, activists in Merauke, officials from the Tourism Office, the Culture Office, the National Border Management Agency in Merauke, students and lecturers from Musamus University. They stated that the festival which had been conducted by the central government seemed in a hurry and lacked coordination with the local government. They also regretted that the festival was dominated by artists from Jakarta, while the local community was less involved. As a result, local cultural and economic potentials are not fully exposed. There are three things that should be considered to promote the border area through festivals: 1) the social, cultural and economic potential of the local community must be the main points promoted, 2) the widespread use of mass media, and 3) the strengthening of networks between the community and the local university, and local government for continual assistance